Preparation process of all-solid-waste environment-friendly road stone based on phosphogypsum

By dehydrating, calcining and modifying the phosphogypsum, compounding it with solid waste materials, adding green bio-based binder and nano calcium carbonate, the problems of strong water absorption and poor mechanical properties of phosphogypsum are solved, and the road is realized The high efficiency, environmental protection, long life and economical applicability of stone.

CN119409470APending Publication Date: 2025-02-11ZHEJIANG WEIHANG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411506276.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, phosphogypsum has strong water absorption, poor mechanical properties, low resource utilization, high energy consumption and large carbon emissions during road materials production.

Method used

By dehydrating phosphogypsum, high-temperature calcining and sodium silicate modification treatment, α-semi-water gypsum is formed, and it is compounded with solid waste materials such as construction waste, fly ash, slag, waste glass powder, etc., and added with green bio-based bonding. The agent and nano calcium carbonate are vacuum homogenized and formed by multi-layer molds, and finally steam and natural curing are carried out.

Benefits of technology

It significantly improves the compressive strength, durability, toughness and water resistance of road stones, reduces dependence on natural resources, and has a high degree of environmental protection and economical applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409470A_ABST
    Figure CN119409470A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of road stone preparation, and discloses a phosphogypsum-based all-solid waste environment-friendly road stone preparation process, which comprises: 1, carrying out a dehydration treatment on phosphogypsum to reduce the free water content to less than 1.5%; step 2, carrying out high-temperature calcination on the dehydrated phosphogypsum in a temperature range of 650 DEG C to 750 DEG C to form alpha-semi-hydrated gypsum; 3, adding a sodium silicate solution into the calcined ardealite for chemical modification to generate calcium silicate gel, so as to improve the water resistance and shrinkage resistance of the calcium silicate gel; and step 4, adding solid waste materials such as the building waste, the fly ash, the slag and the waste glass powder into the phosphogypsum according to a given proportion, crushing and uniformly mixing. The ardealite and the solid waste material are compounded, and an optimized process of a green bio-based binder and a nano material is adopted, so that the mechanical property, the water resistance, the toughness and the weather resistance of the road stone are remarkably improved, and the road stone has the advantages of high efficiency, environment friendliness, long service life, economy and applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pavement stone preparation, and in particular to a full-solid waste and environmentally friendly pavement stone preparation process based on phosphogypsum. Background Art

[0002] With the rapid development of society and the acceleration of urbanization, the amount of solid waste such as construction waste and industrial waste has increased significantly. How to effectively utilize these solid wastes has become a key issue of global concern. At the same time, as an industrial by-product, phosphogypsum is produced in large quantities in the production process of phosphate fertilizers and phosphoric acid. The mountains of phosphogypsum not only occupy land resources, but also pose potential environmental pollution risks. At present, the comprehensive utilization rate of phosphogypsum is low. Most of the phosphogypsum is piled up or simply landfilled without treatment, which is difficult to meet environmental protection requirements and poses a threat to the environment and ecosystem.

[0003] On the other hand, as an important part of infrastructure, road construction has increasingly higher requirements for building materials. Traditional road stones (road paving materials) mostly use cement, lime and other materials, but these materials not only consume a lot of energy and have high carbon emissions during the production process, but also face problems of resource shortage and rising costs. With the global emphasis on sustainable development and environmental protection, how to find a road material that can replace traditional materials and has higher performance has become a research focus.

[0004] In the prior art, attempts have been made to use phosphogypsum in certain road materials, but the common problem is that it has strong water absorption and poor mechanical properties. It is easy to expand and crack under the action of moisture or water, and it is difficult to meet the durability and compressive strength requirements in road use. In addition, the existing phosphogypsum processing process is mostly simple curing or blending, which fails to effectively modify and improve the performance of phosphogypsum, resulting in its application being limited under high humidity or high load conditions. In addition, the existing solid waste material utilization technology is mostly limited to the use of a single material, and fails to fully utilize a variety of industrial wastes in a composite manner, resulting in low resource utilization.

[0005] At the same time, the production process of existing road materials generally relies on traditional cement-based binders, which consume a lot of energy and are accompanied by high carbon dioxide emissions, making it difficult to meet increasingly stringent environmental protection requirements. With the increasing demand for environmental protection and energy conservation, it is particularly urgent to develop an environmentally friendly, efficient and waste-resource-capable road material. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a full-solid waste and environmentally friendly road stone preparation process based on phosphogypsum, which solves the problems in the prior art of strong water absorption, poor mechanical properties, low resource utilization rate of phosphogypsum, high energy consumption and large carbon emissions in the production process of road materials.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: a full solid waste environmentally friendly road stone preparation process based on phosphogypsum, comprising the following steps:

[0008] Step 1: Dehydrating the phosphogypsum to reduce the free moisture content to below 1.5%;

[0009] Step 2: calcining the dehydrated phosphogypsum at a temperature ranging from 650° C. to 750° C. to form α-hemihydrate gypsum;

[0010] Step 3: adding sodium silicate solution to the calcined phosphogypsum for chemical modification to generate calcium silicate gel to improve its water resistance and shrinkage resistance;

[0011] Step 4: adding solid waste materials such as construction waste, fly ash, slag and waste glass powder into phosphogypsum in a predetermined proportion, crushing and evenly mixing;

[0012] Step 5: adding a green bio-based binder, wherein the binder is compounded from enzymatically hydrolyzed soy protein and chitosan;

[0013] Step 6: Vacuum homogenize the mixture to remove bubbles and increase the density of the material;

[0014] Step 7: Pour the treated mixture into a multi-layer mold for compression molding, compacting layer by layer, wherein the bottom layer is a high-density layer, the middle layer is a toughness enhancement layer, and the surface layer is a water-resistant layer;

[0015] Step 8: Steam and naturally cure the formed road stones to solidify and stabilize them. Preferably, in the dehydration step, the phosphogypsum is treated by an intermittent vacuum evaporation system, the evaporation temperature of the system is set to 90°C, the vacuum degree is set to -0.08MPa, and the dehydration time is 2 hours to ensure that the free water content in the phosphogypsum is reduced to below 1.5%.

[0016] Preferably, in the high-temperature calcination step, the calcination temperature of the phosphogypsum is controlled between 650°C and 750°C, and the calcination time is 2 hours, so that its crystal structure is converted into α-hemihydrate gypsum, and then slowly cooled to room temperature to avoid material structure instability caused by rapid cooling.

[0017] Preferably, in the step of adding sodium silicate solution to the calcined phosphogypsum for chemical modification, the concentration of the sodium silicate solution is 3%-5%, the stirring reaction temperature is 40°C, and the reaction time is 20 minutes, ensuring the generation of calcium silicate gel to enhance the water resistance and shrinkage resistance of the material.

[0018] Preferably, the green bio-based binder is made of a composite of enzymatically hydrolyzed soy protein and modified chitosan in a mass ratio of 3:1, wherein the enzymatically hydrolyzed soy protein is subjected to low-temperature enzymatic hydrolysis by papain at 45°C for 4 hours, and the chitosan is modified by adding 0.5%-1% of dextran.

[0019] Preferably, the solid waste materials include construction waste, fly ash, slag and waste glass powder, with construction waste accounting for 20%-25% of the total weight of the mixture, fly ash accounting for 10%-15%, slag accounting for 10%-15%, and waste glass powder accounting for 5%-8%. The solid waste materials are crushed into uniform particles through a 120-mesh sieve and fully mixed with phosphogypsum.

[0020] Preferably, in the vacuum homogenization step, the vacuum degree is set to -0.1 MPa, the processing time is 15 minutes, and the processing is carried out by ultrasonic dispersion equipment to ensure that the nano calcium carbonate particles are evenly dispersed in the mixture, thereby improving the density and compression resistance of the mixture.

[0021] Preferably, in the pressing step, the molding mold has a three-layer structure, the bottom layer is 30 mm thick and is a high-density pressure-resistant layer; the middle layer is 20 mm thick and 5% of plant fiber is added to enhance toughness; the surface layer is 10 mm thick and chitosan modified material is added to enhance water resistance, and is compacted layer by layer.

[0022] Preferably, the initial pressure during the pressing process is set to 20 MPa, the final pressing force is 60 MPa, the pressing time is controlled to 10 minutes, and the gradually increasing pressing force ensures that the density of each layer of material is uniform and the structure is stable.

[0023] Preferably, in the steam curing step, the curing temperature is set to 80° C. and the duration is 12 hours; in the natural curing step, the natural curing time is 7 to 14 days.

[0024] The present invention provides a process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum.

[0025] Beneficial effects:

[0026] 1. The present invention uses phosphogypsum and a variety of solid waste materials as the main raw materials, making full use of industrial by-products and construction waste. This process not only reduces the accumulation and environmental pollution of industrial waste such as phosphogypsum, but also realizes waste resource utilization, effectively reduces dependence on natural resources, and is highly environmentally friendly.

[0027] 2. The present invention converts phosphogypsum into α-hemihydrate gypsum by dehydration, high-temperature calcination and sodium silicate modification, which greatly improves the compressive strength and durability of the material. Experimental data show that the compressive strength of the road stone prepared by the present invention can reach 40MPa, which is much higher than the 25MPa in the traditional process, and significantly improves the bearing capacity of the material in road construction.

[0028] 3. The use of the green bio-based binder of the present invention makes the material have good toughness and crack resistance. Combined with reinforcing materials such as plant fibers, the road stone can maintain structural integrity under repeated loads or extreme environments, avoiding the defect of traditional road stones that are prone to cracking due to brittleness.

[0029] 4. The present invention uses sodium silicate to modify phosphogypsum and adds nano calcium carbonate, so that the water absorption rate of the pavement prepared by the present invention is as low as 3%. This low water absorption allows the material to maintain structural stability in a humid or rainy environment, and will not cause expansion, cracking or structural failure due to water penetration, which significantly improves the durability and applicability of the pavement.

[0030] 5. The present invention combines multi-layer composite structure design with steam and natural curing to enable the road stone to remain stable for a long time under complex climatic conditions. After 100 freeze-thaw cycle tests, the mass loss rate of the material is only 0.5%, which is significantly higher than the weather resistance of traditional materials, ensuring that it is not easy to crack or damage in an environment with a sharp temperature difference.

[0031] 6. The steps of the present invention are clear and controllable. Through the process of dehydration calcination, modification treatment, binder compounding, vacuum homogenization treatment, mold forming and maintenance, the material performance is effectively improved, and it is suitable for industrial large-scale production. The equipment and process used can be widely used in existing industrial production lines, with high economy and feasibility.

[0032] In summary, the present invention significantly improves the mechanical properties, water resistance, toughness and weather resistance of road stones by compounding phosphogypsum with solid waste materials and adopting the optimized process of green bio-based binders and nanomaterials, and has the advantages of high efficiency, environmental protection, long life and economic applicability. These beneficial effects make the process of the present invention have great application potential in road construction and related fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1:

[0036] Please see attached Figure 1 The embodiment of the present invention provides a full solid waste environmentally friendly road stone preparation process based on phosphogypsum, comprising the following steps:

[0037] 1. Dehydration and calcination of phosphogypsum

[0038] 1.1 Dehydration of phosphogypsum

[0039] In this embodiment, phosphogypsum containing free water is used as the main raw material. 1000 kg of phosphogypsum is put into an intermittent vacuum evaporation system. The system is set up as follows: the evaporation temperature is 90°C and the vacuum degree is set to -0.08MPa. Under this temperature and vacuum conditions, the evaporation system can remove moisture from the phosphogypsum at a lower temperature to avoid high temperature damaging the effective ingredients in the phosphogypsum. The evaporation process lasts for 2 hours, during which the water evaporation rate needs to be continuously monitored to ensure that the free water content drops below 1.5%. This step is to ensure that the mechanical properties and processing characteristics of the material will not be affected by excess moisture in subsequent processes.

[0040] 1.2 Calcination treatment

[0041] The dehydrated phosphogypsum enters a high-temperature calcining furnace for high-temperature treatment. The temperature of the calcining furnace is set at 650°C to 750°C and maintained at a constant temperature for 2 hours. The purpose of high-temperature calcination is to convert the crystal structure of phosphogypsum into α-hemihydrate gypsum, which has higher density and compressive resistance. In order to avoid unstable material structure due to rapid cooling, it needs to be slowly cooled to room temperature after calcination. This slow cooling process helps to maintain the density of the material and provide a stable substrate for subsequent processes.

[0042] Through strict temperature and vacuum control, the moisture content of phosphogypsum is reduced to a safe level, and the transformation of the crystal structure after calcination improves the mechanical properties of the material, laying a solid foundation for subsequent bonding and composite processes.

[0043] 2. Modification of phosphogypsum by sodium silicate solution

[0044] In this embodiment, after the calcination treatment is completed, the water resistance of the phosphogypsum is further improved by chemical modification. The specific steps are as follows: the calcined phosphogypsum is mixed with a 3%-5% concentration of sodium silicate solution at 5% of the weight of the phosphogypsum. The mixing is carried out at 40°C and stirred for 20 minutes to ensure sufficient reaction. Sodium silicate reacts with calcium ions in phosphogypsum to form calcium silicate gel. The formed calcium silicate gel can significantly improve the water resistance and structural stability of the material, and reduce the expansion and cracking of the material in a humid environment.

[0045] By adding sodium silicate solution, the water resistance and weather resistance of phosphogypsum are greatly improved, making it suitable for road construction exposed to humid or rainy environments for a long time. This chemical modification improves the dimensional stability of phosphogypsum under external pressure or humidity changes.

[0046] 3. Composite treatment of solid waste materials

[0047] 3.1 Screening and crushing of solid waste materials

[0048] In this embodiment, construction waste, fly ash, slag and waste glass powder are used as solid waste raw materials for compounding. The specific ratio is: construction waste accounts for 20%-25% of the total mixture weight, fly ash accounts for 10%-15%, slag accounts for 10%-15%, and waste glass powder accounts for 5%-8%. These materials are all refined by a mechanical crusher and sieved through a 120-mesh screen to ensure that their particle size is uniform and can be fully mixed with phosphogypsum and other binders. The particle size of the crushed material is controlled between 50 microns and 100 microns to ensure the fluidity and mechanical properties of the mixed material.

[0049] 3.2 Addition and dispersion of nano calcium carbonate

[0050] In order to improve the compactness and compressive strength of the composite material, 1%-2% of nano calcium carbonate is added in this embodiment. Nano calcium carbonate has a high specific surface area and activity and can fill the microscopic pores in the mixture. In order to ensure that the nano calcium carbonate is evenly distributed, an ultrasonic dispersion device is used for processing, and the dispersion time is set to 15 minutes to ensure that all particles are evenly distributed and avoid aggregation.

[0051] By introducing solid waste materials such as construction waste and fly ash, the production cost is reduced and industrial waste is effectively utilized. At the same time, the addition of nano calcium carbonate significantly improves the density and compressive strength of the material, making the prepared road stone more durable.

[0052] 4. Preparation and use of green bio-based binders

[0053] 4.1 Enzymatic hydrolysis of soy protein

[0054] In this embodiment, soy protein is selected as the main raw material of the adhesive. First, 100 kg of soy protein powder is placed in a reactor, and a certain amount of water is added to prepare a soy protein solution with a concentration of 20%. Then, 0.5% papain is added and low-temperature enzymolysis is performed at 45°C for 4 hours. The enzymolysis reaction can destroy the complex macromolecular structure in soy protein, generate short peptides and small molecular amino acids, thereby improving its bonding performance.

[0055] 4.2 Modification of chitosan

[0056] When preparing chitosan modified binder, 0.5%-1% glucan is used for modification in this embodiment. First, a 2% chitosan solution is prepared, stirred at 40°C, and the glucan solution is added and stirred for 30 minutes until the molecular structure of chitosan is optimized to enhance its water solubility and bonding performance. The modified chitosan and enzymatically hydrolyzed soy protein are compounded in a ratio of 3:1 to form a green bio-based binder.

[0057] 4.3 Use of adhesive

[0058] The final green bio-based binder is added to the solid waste phosphogypsum mixture at 5%-8% of the total weight of the mixture to ensure its uniform distribution throughout the composite material and improve the bonding strength and toughness of the material.

[0059] Green bio-based adhesives not only provide good bonding strength, but also meet environmental protection requirements. The synergistic effect of enzymatically hydrolyzed soy protein and chitosan improves the material's bonding, water resistance and biodegradability, effectively reducing environmental pollution.

[0060] 5. Vacuum homogenization

[0061] In this embodiment, after the phosphogypsum, solid waste materials and binder are mixed, they enter the vacuum homogenization equipment for treatment. The vacuum degree is set to -0.1MPa and the treatment time is 15 minutes. Through vacuum homogenization treatment, bubbles in the mixture can be effectively removed, and the density and mechanical properties of the material can be improved. This treatment further ensures the uniform distribution of nano calcium carbonate and other granular materials in the entire mixture through an ultrasonic dispersion system.

[0062] Vacuum homogenization not only improves the density of the material, reduces the voids in the material, and makes the material have higher compressive strength and toughness. In addition, the homogenization process also improves the durability of the material and ensures the mechanical stability of the final product.

[0063] 6. Mould forming and pressing

[0064] 6.1 Moulding

[0065] In this embodiment, a multi-layer mold structure is used for material molding. The bottom layer is a high-density compression layer with a thickness of 30 mm; the middle layer is a toughness enhancement layer with a thickness of 20 mm and 5% plant fiber (such as hemp fiber) is added; the surface layer is a water-resistant layer with a thickness of 10 mm and chitosan modified binder is added. The mixture is added to the mold layer by layer, and each layer of material needs to be compacted after addition to ensure the density and uniformity of each layer of material.

[0066] 6.2 Pressing process

[0067] During the molding process, a hydraulic press is used for step-by-step pressing, with the initial pressure set at 20MPa, the final pressing force at 60MPa, and the pressing time controlled at 10 minutes. This pressing process ensures that the density of each layer of material is uniform, and the entire multi-layer structure forms a whole without delamination or gaps.

[0068] The multi-layer molding design enables the road stone to have different levels of functions, such as high compressive resistance of the bottom layer, enhanced toughness of the middle layer and water resistance of the surface layer. This multi-layer structure not only extends the service life of the material, but also improves its adaptability in complex road environments.

[0069] 7. Maintenance and curing

[0070] 7.1 Steam curing

[0071] In this embodiment, the formed pavement is first subjected to steam curing. The finished product is placed in a steam environment at 80°C for 12 hours. Steam curing helps accelerate the curing reaction of the soy protein and chitosan binder and improve the initial strength of the material.

[0072] 7.2 Natural maintenance

[0073] After steam curing, the road stone is placed in a natural environment for curing for 7 to 14 days. The purpose of natural curing is to allow the moisture inside the material to gradually evaporate, further improving its structural stability and mechanical properties.

[0074] Steam curing provides a rapid curing effect, allowing the material to gain initial strength in a short period of time, while natural curing ensures the long-term stability of the material, avoiding cracks or structural instability caused by uneven moisture evaporation.

[0075] Embodiment 2:

[0076] In this embodiment 2, the process used is basically the same as that of embodiment 1, and only one improvement is made to the formula of the green bio-based binder. The main purpose of embodiment 2 is to verify the optimal formula configuration in embodiment 1 by changing the ratio of the binder. The following are the detailed steps:

[0077] 1. Dehydration and calcination of phosphogypsum

[0078] In this embodiment 2, the dehydration and calcination steps of phosphogypsum are exactly the same as those in embodiment 1. The specific steps are as follows: 1.1 Dehydration treatment of phosphogypsum: Use an intermittent vacuum evaporation system with the temperature set at 90°C and the vacuum degree at -0.08MPa for 2 hours to reduce the free water content in the phosphogypsum to below 1.5%. 1.2 Calcination treatment: Calcine the dehydrated phosphogypsum at a temperature range of 650°C to 750°C for 2 hours, and slowly cool to room temperature after calcination to obtain α-hemihydrate gypsum.

[0079] 2. Modification of phosphogypsum by sodium silicate solution

[0080] In the second embodiment, the modification steps of phosphogypsum are also exactly the same as those in the first embodiment. The specific steps are: adding 3%-5% sodium silicate solution at 5% of the weight of phosphogypsum, and stirring at 40°C for 20 minutes to generate calcium silicate gel, thereby improving the water resistance and shrinkage resistance of phosphogypsum.

[0081] 3. Composite treatment of solid waste materials

[0082] In the second embodiment, the compounding steps of the solid waste materials remain unchanged. As in the first embodiment, construction waste, fly ash, slag and waste glass powder are mixed in the same proportion, and 1%-2% nano calcium carbonate is added using ultrasonic dispersion technology to improve the mechanical properties of the material.

[0083] 4. Preparation and use of green bio-based binders

[0084] In the second embodiment, the ratio of the green bio-based binder is different, which is used as the main variable for comparison:

[0085] 4.1 Soybean protein hydrolysis

[0086] In the second embodiment, soybean protein is still used as the main binder. 100 kg of soybean protein powder is placed in a reactor, 20% of water is added to prepare a soybean protein solution, and 0.5% of papain is added to perform enzymolysis at 45° C. for 4 hours.

[0087] 4.2 Chitosan modification

[0088] The modification treatment of chitosan remains consistent, and chitosan is modified with 0.5%-1% dextran to improve its water solubility and bonding properties.

[0089] 4.3 Adjustment of binder ratio

[0090] Different from Example 1, the ratio of soy protein to chitosan in Example 2 is 2:1, instead of 3:1 in Example 1. The adjusted green bio-based binder is added to the mixture of phosphogypsum and solid waste materials at 5%-8% of the total weight of the mixture.

[0091] The purpose of the change in the binder ratio in the second embodiment is to improve the adhesive ability of the binder by increasing the proportion of soy protein. However, this adjustment may also cause changes in other properties (such as toughness, weather resistance, etc.).

[0092] 5. Vacuum homogenization

[0093] The vacuum homogenization process is the same as that in Example 1, with the vacuum degree set to -0.1 MPa and the processing time being 15 minutes. Through this processing step, the nano calcium carbonate is ensured to be uniformly dispersed and bubbles in the mixture are removed.

[0094] 6. Mould forming and pressing

[0095] The mold forming and pressing steps are consistent with those in Example 1. The specific steps are as follows:

[0096] A multi-layer mold is used, with the bottom layer being a high-density pressure-resistant layer, the middle layer being a toughness-enhancing layer, and the surface layer being a water-resistant layer. Each layer of material is compacted layer by layer.

[0097] The pressing process adopts step-by-step pressing, with the initial pressing force set at 20MPa, the final pressing force at 60MPa, and the pressing time at 10 minutes to ensure that the material is uniform and dense.

[0098] 7. Maintenance and curing

[0099] The curing and curing steps are consistent with those in Example 1, and the specific steps are as follows:

[0100] Steam curing: Place the formed pavement in a 80℃ steam environment for curing for 12 hours.

[0101] Natural curing: After steam curing, place it in a natural environment for 7 to 14 days to ensure that the moisture in the material is fully evaporated and further improve its mechanical properties.

[0102] Embodiment three:

[0103] In this embodiment 3, the process is basically the same as that of the embodiment 1, and the only variable is the addition ratio of nano calcium carbonate. This embodiment is intended to verify the effect of different addition amounts of nano calcium carbonate on the mechanical properties and structural stability of the pavement, and further prove that the addition ratio of nano calcium carbonate (1%-2%) in the embodiment 1 is the best preferred ratio. The following are the specific steps:

[0104] 1. Dehydration and calcination of phosphogypsum

[0105] In this embodiment three, the dehydration and calcination steps of phosphogypsum are the same as those in embodiment one, which are as follows: 1.1 Dehydration treatment of phosphogypsum: an intermittent vacuum evaporation system is used, the temperature is set to 90°C, the vacuum degree is -0.08MPa, and the treatment time is 2 hours to reduce the free water content in the phosphogypsum to below 1.5%.

[0106] 1.2 Calcination treatment: The dehydrated phosphogypsum is calcined at a temperature range of 650°C to 750°C for 2 hours, and then slowly cooled to room temperature to obtain α-hemihydrate gypsum.

[0107] 2. Modification of phosphogypsum by sodium silicate solution

[0108] The modification treatment of phosphogypsum is the same as that in Example 1: a 3%-5% sodium silicate solution is added at 5% of the weight of the phosphogypsum and stirred at 40°C for 20 minutes to allow it to fully react to generate calcium silicate gel, thereby improving the water resistance and shrinkage resistance of the phosphogypsum.

[0109] 3. Composite treatment of solid waste materials

[0110] In the third embodiment, the steps for composite treatment of solid waste materials are the same as those in the first embodiment. Construction waste, fly ash, slag and waste glass powder are mixed in the following proportions:

[0111] Construction waste: 20%-25%

[0112] Fly ash: 10%-15%

[0113] Slag: 10%-15%

[0114] Waste glass powder: 5%-8%

[0115] All solid waste materials were screened through a 120-mesh screen to ensure uniform particles and crushed to a particle size of 50-100 microns.

[0116] 4. Preparation and use of green bio-based binders

[0117] In this embodiment 3, the preparation of the green bio-based binder is consistent with that of the embodiment 1, as follows:

[0118] After low-temperature enzymatic hydrolysis (45°C, 4 hours), the soy protein was mixed with the modified chitosan in a ratio of 3:1.

[0119] Chitosan is modified with 0.5%-1% dextran to improve its water solubility and bonding properties.

[0120] The binder is added to the mixture of phosphogypsum and solid waste material at 5% to 8% of the total weight of the mixture.

[0121] 5. Addition and dispersion of nano calcium carbonate (adjustment variables)

[0122] In this Example 3, the only variable is the addition ratio of nano calcium carbonate is different from that of Example 1. The addition ratio of nano calcium carbonate is 0.5%-1% (compared to 1%-2% in Example 1), and it is evenly dispersed by ultrasonic dispersion equipment. The ultrasonic dispersion time is 15 minutes to ensure that the nano calcium carbonate can be evenly distributed in the mixture of solid waste material and phosphogypsum.

[0123] The third embodiment aims to reduce the addition ratio of nano calcium carbonate to observe its influence on the density, compressive strength and overall mechanical properties of the mixture.

[0124] 6. Vacuum homogenization

[0125] The vacuum homogenization treatment step is consistent with that in Example 1, the vacuum degree is set to -0.1 MPa, and the treatment time is 15 minutes. In this step, bubbles are removed by vacuum treatment to improve the density and uniformity of the mixture.

[0126] 7. Mould forming and pressing

[0127] The mold forming and pressing steps are the same as those in Example 1, and a multi-layer structure is adopted, as follows:

[0128] The bottom layer is a high-density compression-resistant layer with a thickness of 30 mm;

[0129] The middle layer is a toughness-enhancing layer with a thickness of 20 mm and 5% plant fiber added;

[0130] The surface layer is a water-resistant layer with a thickness of 10 mm and chitosan modified material is added.

[0131] During the molding process, a hydraulic press is used for step-by-step pressing, with the initial pressure set to 20 MPa, the final pressing force to 60 MPa, and the pressing time to 10 minutes.

[0132] 8.Curation and curing

[0133] The curing and solidification steps are consistent with those in Example 1 and are divided into two steps:

[0134] Steam curing: Steam curing for 12 hours at 80°C ensures rapid curing of the adhesive.

[0135] Natural curing: After steam curing, the material is placed in a natural environment for 7 to 14 days to ensure the stability of the internal structure.

[0136] Experimental example:

[0137] Experimental Materials:

[0138] Example 1: The binder ratio is 3:1 of soybean protein and chitosan, and the addition ratio of nano calcium carbonate is 1%-2%.

[0139] Example 2: The binder ratio is 2:1 of soybean protein and chitosan, and the addition ratio of nano calcium carbonate is 1%-2%.

[0140] Example 3: The binder ratio is 3:1 of soybean protein and chitosan, and the addition ratio of nano calcium carbonate is 0.5%-1%.

[0141] Experimental steps:

[0142] 1. Material Preparation

[0143] According to the recipes and steps of various examples, three mixtures with different recipes were prepared.

[0144] The same mold, pressing process, molding conditions, and curing steps were used to ensure that all conditions except the variables remained consistent during the experiment.

[0145] 2. Experimental Project

[0146] After each type of pavement stone sample is produced, the following performance tests are carried out:

[0147] Compressive strength test: Use a compressive strength tester to test the maximum strength of the pavement under vertical pressure.

[0148] Toughness test: Cyclic load testing measures the durability and crack resistance of a material under repeated application of a certain load.

[0149] Water absorption test: Soak the pavement stone samples for 72 hours and test their water absorption.

[0150] Freeze-thaw cycle test: Through 100 freeze-thaw cycles, the quality loss of the material in an extreme temperature difference environment is tested.

[0151] Table 1 Comparison table of experimental data of embodiment

[0152]

[0153] Experimental results and analysis:

[0154] Compressive strength: Example 1 performs best, with a compressive strength of 40 MPa, significantly higher than Example 2 (35 MPa) and Example 3 (32 MPa). This is because the addition ratio of nano-calcium carbonate (1%-2%) in Example 1 makes the mixture more compact, while the binder ratio in Example 2 and the reduction of nano-calcium carbonate in Example 3 both lead to a decrease in compressive strength.

[0155] Toughness: Example 1 has the best toughness performance, with a crack rate of less than 5%. Example 2 has a crack rate of 10%, and Example 3 has a crack rate of 20%, indicating that reducing the proportion of chitosan or nano-calcium carbonate will significantly reduce the durability and crack resistance of the material.

[0156] Water absorption: Example 1 has the lowest water absorption (3%), proving its best water resistance. Example 2 has a water absorption of 4.5%, and Example 3 has a water absorption of 5%, indicating that the reduction of the binder ratio and nano-calcium carbonate will increase the water absorption of the material.

[0157] Freeze-thaw cycle loss rate: The freeze-thaw loss rate of Example 1 is only 0.5%, which is much lower than 1% of Example 2 and 1.5% of Example 3. This shows that the material of Example 1 has the strongest durability in an extreme temperature difference environment.

[0158] Through synchronous experiments, the best optimization effect of Example 1 was verified. Experimental data show that Example 1 performs well in compressive strength, toughness, water absorption and freeze-thaw loss, especially compressive strength and durability are significantly better than Example 2 and Example 3. The optimal addition ratio of nano calcium carbonate (1%-2%) and the optimal ratio of binder (3:1 soy protein and chitosan) are crucial to the comprehensive performance of the final roadstone.

[0159] Comparative Example 1:

[0160] In order to further verify the superiority of Example 1, this article also provides a comparative example of a traditional process. The traditional process mainly uses unmodified phosphogypsum and does not use green bio-based binders and nano calcium carbonate. This comparative solution is usually used to produce basic road stones, but its mechanical properties and durability are relatively low.

[0161] 1. Raw material selection and processing

[0162] In the traditional process, natural dihydrate phosphogypsum is used as raw material without dehydration treatment.

[0163] Phosphogypsum: Dihydrate phosphogypsum that has not been dehydrated or calcined is used, containing about 5%-7% free water.

[0164] Solid waste materials: construction waste, fly ash and slag are still used, but waste glass powder and nano calcium carbonate are not added. The proportion of construction waste and fly ash is similar to that in the embodiment, construction waste accounts for 20%-25%, fly ash and slag each accounts for 10%-15%.

[0165] 2. Binder

[0166] In traditional processes, cement or lime is used as a binder instead of a green bio-based binder.

[0167] Cement or lime: Ordinary cement or lime was added as a binder with a cement ratio of 10% without any biomodification treatment.

[0168] 3. Mixing and molding

[0169] Mixing: Phosphogypsum, solid waste materials and cement are simply mechanically stirred at room temperature without vacuum homogenization. Since the mixture contains more free water, its density is poor and bubbles are easily generated during the mixing process.

[0170] Molding: Pour the mixture into a mold and use a simple pressing process with a pressing force of 20MPa.

[0171] 4. Maintenance

[0172] The maintenance method in traditional technology is relatively simple:

[0173] Natural curing: The formed road stones are naturally cured without using steam curing technology. The natural curing time is 14 days.

[0174] Table 2 Comparison table of comparative experimental data

[0175]

[0176]

[0177] Data Analysis:

[0178] Compressive strength:

[0179] The unmodified phosphogypsum and cement binder used in the conventional process resulted in a significantly lower compressive strength of only 25 MPa. Compared with Example 1 (40 MPa), the conventional road stone was easily broken when subjected to vertical pressure and the structure was not strong enough.

[0180] toughness:

[0181] The toughness performance of the traditional process is poor, with a crack rate of 30%. Cracks are prone to occur under multiple cyclic loads. The durability and crack resistance of the material are far inferior to those of Example 1.

[0182] Water absorption:

[0183] The water absorption rate of the traditional process is 8%, which is significantly higher than 3% in Example 1. This is because the traditional process does not perform dehydration and modification of phosphogypsum, and does not add nano calcium carbonate and green bio-based binder, which makes the material easy to expand and crack after absorbing water.

[0184] Freeze-thaw loss rate:

[0185] The freeze-thaw cycle loss rate of the conventional process is 3%, which is significantly higher than 0.5% of Example 1. Conventional materials are prone to cracking under extreme temperature difference conditions, and the long-term weather resistance of the materials is relatively poor.

[0186] By comparing Example 1 with the traditional process, it can be seen that the various performance indicators of Example 1 are better than those of the traditional process. The process of Example 1 greatly improves the compressive strength, toughness, water absorption and weather resistance of the material by dehydrating and modifying phosphogypsum, adding nano calcium carbonate and using green bio-based binders, while the road stone of the traditional process performs poorly in these properties. Therefore, the process of Example 1 not only has significant advantages in environmental protection, but also shows better mechanical properties and long-term use stability in practical applications.

[0187] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum, characterized in that: The following steps are involved: Step 1: Dehydrating the phosphogypsum to reduce the free moisture content to below 1.5%; Step 2: calcining the dehydrated phosphogypsum at a temperature ranging from 650° C. to 750° C. to form α-hemihydrate gypsum; Step 3: adding sodium silicate solution to the calcined phosphogypsum for chemical modification to generate calcium silicate gel to improve its water resistance and shrinkage resistance; Step 4: adding solid waste materials such as construction waste, fly ash, slag and waste glass powder into phosphogypsum in a predetermined proportion, crushing and evenly mixing; Step 5: adding a green bio-based binder, wherein the binder is compounded from enzymatically hydrolyzed soy protein and chitosan; Step 6: Vacuum homogenize the mixture to remove bubbles and increase the density of the material; Step 7: Pour the treated mixture into a multi-layer mold for compression molding, compacting layer by layer, wherein the bottom layer is a high-density layer, the middle layer is a toughness enhancement layer, and the surface layer is a water-resistant layer; Step 8: Steam cure and natural cure the formed road stones to make them solid and stable.

2. The process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum according to claim 1, characterized in that: In the dehydration treatment step, the phosphogypsum is treated by an intermittent vacuum evaporation system, the evaporation temperature of the system is set to 90°C, the vacuum degree is set to -0.08MPa, and the dehydration time is 2 hours to ensure that the free water content in the phosphogypsum is reduced to below 1.5%.

3. The process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum according to claim 1, characterized in that: In the high-temperature calcination step, the calcination temperature of the phosphogypsum is controlled between 650°C and 750°C, and the calcination time is 2 hours, so that its crystal structure is converted into α-hemihydrate gypsum, and then slowly cooled to room temperature to avoid material structure instability caused by rapid cooling.

4. The process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum according to claim 1, characterized in that: In the step of adding sodium silicate solution to the calcined phosphogypsum for chemical modification, the concentration of the sodium silicate solution is 3%-5%, the stirring reaction temperature is 40°C, and the reaction time is 20 minutes, ensuring the generation of calcium silicate gel to enhance the water resistance and shrinkage resistance of the material.

5. The process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum according to claim 1, characterized in that: The green bio-based binder is prepared by compounding enzymatically hydrolyzed soy protein and modified chitosan in a mass ratio of 3:1, wherein the enzymatically hydrolyzed soy protein is subjected to low-temperature enzymatic hydrolysis at 45° C. for 4 hours by papain, and the chitosan is modified by adding 0.5%-1% of glucan.

6. The process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum according to claim 1, characterized in that: The solid waste materials include construction waste, fly ash, slag and waste glass powder, with construction waste accounting for 20%-25% of the total weight of the mixture, fly ash accounting for 10%-15%, slag accounting for 10%-15%, and waste glass powder accounting for 5%-8%. The solid waste materials are crushed into uniform particles through a 120-mesh sieve and fully mixed with phosphogypsum.

7. The process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum according to claim 1, characterized in that: In the vacuum homogenization step, the vacuum degree is set to -0.1 MPa, the processing time is 15 minutes, and the processing is performed by ultrasonic dispersion equipment to ensure that the nano calcium carbonate particles are evenly dispersed in the mixture, thereby improving the density and compression resistance of the mixture.

8. The process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum according to claim 1, characterized in that: In the pressing step, the molding mold has a three-layer structure, the bottom layer is 30 mm thick and is a high-density compression-resistant layer; the middle layer is 20 mm thick and 5% of plant fiber is added to enhance toughness; the surface layer is 10 mm thick and chitosan modified material is added to enhance water resistance, and is compacted layer by layer.

9. The process for preparing all-solid waste environmentally friendly road stone based on phosphogypsum according to claim 1, characterized in that: The initial pressure during the pressing process is set to 20 MPa, the final pressing force is 60 MPa, the pressing time is controlled to be 10 minutes, and the gradually increasing pressing force ensures that the density of each layer of material is uniform and the structure is stable.

10. The all-solid waste environmentally friendly road stone preparation process based on phosphogypsum according to claim 1, characterized in that: In the steam curing step, the curing temperature is set to 80° C. and the duration is 12 hours; in the natural curing step, the natural curing time is 7 to 14 days.